Anthielmintic efficiency of Disofenol and Niclofolan in cattle - Echevarria, Flávio A.; Pinheiro, Alfredo C. (Pesquisa Agropecuaria Brasileira, 2014)
Observations were performed to determine the efficiency of Disofenol and Niclofolan against mature form of Fasciola hepatica (Lin.1758) in cattle. Disotenol was used at 20% in dosis of 8.27 mg/kg and Niclofolan at 4% in dosis of 0.86 mg/kg. The results show that Disofenol was less effective (55,9%) against mature fasciola than Niclofolan (96,9).